The Relationship Between Capital Flows and Current Deficit : Evidence from Turkey - Akbas, Yusuf Ekrem; Senturk, Mehmet; Sancar, Canan (Indian Journal of Finance, 2014)
The present paper analyzed the relationship between current account deficit and capital flows in Turkey over the period from 1990-2011. Augmented Dickey Fuller and Dickey Fuller-Generalized Least Squares unit root tests were used to analyze the stability of current deficit (CA) and capital flows (CF) series. Then, autoregressive distributed lag (ARDL) bound test was used in order to check if there is cointegration between the series according to the results obtained from the ARDL test. To conclude, the study revealed that is a cointegration relationship between current deficit and capital flows in Turkey.